2019
DOI: 10.4317/medoral.23136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the sleep period and the amount of habitual snoring in individuals with sleep bruxism

Abstract: Background: The literature does not report any association between habitual snoring and sleep bruxism, but these situations can be a reason for frequent complaints of individuals, impairing the quality of life. This study was performed to investigate the sleep period and amount of habitual snoring in individuals with sleep bruxism observing expiratory, inspiratory, and mixed snoring. Material and Methods: A total of 90 individuals were screened and divided into the following groups: with sleep bruxism (n=45) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…Palinkas et al suggested that individuals with SB experience an increased amount of habitual snoring during sleep. The authors recorded the number of inspiratory, expiratory, and mixed snores but did not evaluate the loudness of snores [48]. In the current study, we examined the relationship between SS and SB and their parameters (intensity, frequency, types, and sleep position).…”
Section: Discussionmentioning
confidence: 97%
“…Palinkas et al suggested that individuals with SB experience an increased amount of habitual snoring during sleep. The authors recorded the number of inspiratory, expiratory, and mixed snores but did not evaluate the loudness of snores [48]. In the current study, we examined the relationship between SS and SB and their parameters (intensity, frequency, types, and sleep position).…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between snoring and SB has not yet been thoroughly studied. Palinkas et al investigated the sleep period and the amount of habitual snoring in individuals with SB, and they concluded that sleep bruxers tended to have an increased amount of habitual snoring (Palinkas et al., 2019). Carra et al also indicated a mandibular advancement appliance as a common therapeutic pathway for both snoring and SB (Carra, Huynh, El‐Khatib, Remise, & Lavigne, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Приблизно 50% немовлят мають прояви бруксизму при прорізуванні зубів. Патологічні стани, які можуть бути пов'язані з бруксизмом, включають тривожність, церебральний параліч, розумову відсталість, а також вживання ряду медикаментозних препаратів, зокрема антидепресантів [23]. Гіперсомнії -порушення сну, які характеризуються денною сонливістю і необхідністю додаткового денного відпочинку.…”
Section: рис 2 зміни еег під час розвитку різних фаз снуunclassified